ANALISIS PENDAPATAN USAHA DAGANG BUAH DI KELURAHAN PERKAMIL KOTA MANADO - Marlita ., Dotulong; Martha Mareyke Sendow; Eyverson ., Ruauw (Sam Ratulangi University, 2021)
This study aims to analyze the income of the fruit trading business in the Perkamil Village, Manado City. The research site is located close to the Tikala Sector Police Office, Manado City. The time of the research was carried out for 3 months from December 2020 to February 2021. The data used in this study were primary data and secondary data. Primary data were obtained through interviews with all traders in the location as many as 7 respondents (traders).The analysis used is income analysis. The results showed that the total revenue was greater than the total cost so that the business was profitable and feasible to continue.